2008
DOI: 10.1073/pnas.0803022105
|View full text |Cite
|
Sign up to set email alerts
|

RNAi screening for kinases and phosphatases identifies FoxO regulators

Abstract: Forkhead box class O (FoxO) transcription factors are key regulators of growth, metabolism, life span, and stress resistance. FoxOs integrate signals from different pathways and guide the cellular response to varying energy and stress conditions. FoxOs are modulated by several signaling pathways, e.g., the insulin-TOR signaling pathway and the stress induced JNK signaling pathway. Here, we report a genome wide RNAi screen of kinases and phosphatases aiming to find regulators of dFoxO activity in Drosophila S2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…S2B). In an RNAi screen, depletion of Ire1 was reported to modestly reduce FOXO abundance but not to affect nuclear localization (Mattila et al 2008). We confirmed that depletion of Ire1 by >50% did not affect insulininduced relocalization of FOXO to the cytoplasm or FOXO mislocalization caused by depletion of Hrd3 (Supplemental Fig.…”
Section: Er Stress Acts Via Perk To Regulate Foxo Activitysupporting
confidence: 68%
“…S2B). In an RNAi screen, depletion of Ire1 was reported to modestly reduce FOXO abundance but not to affect nuclear localization (Mattila et al 2008). We confirmed that depletion of Ire1 by >50% did not affect insulininduced relocalization of FOXO to the cytoplasm or FOXO mislocalization caused by depletion of Hrd3 (Supplemental Fig.…”
Section: Er Stress Acts Via Perk To Regulate Foxo Activitysupporting
confidence: 68%
“…Several signaling molecules and pathways have been implicated in the regulation of the subcellular distribution of FoxO3a in various cell types (37)(38)(39)(40), among them JNK (41,42), the p38 MAP kinase (43), and protein phosphatase 2A (44). We found that pharmacological inhibition of JNK, p38 MAP kinase, or protein phosphatase 2A using the JNK-1 inhibitor peptide, SB203580, and okadaic acid, respectively, blocked glutamateinduced nuclear translocation of FoxO3a-GFP in hippocampal neurons (Fig.…”
Section: Depletion Of Foxo3a Protects Against Nmda-induced Cellmentioning
confidence: 67%
“…3, compare panels C and F). Parallel ac76e in situ stainings in the homozygous foxo 25 null mutant and its littermate control strain, EP-147 (20), demonstrated a clear reduction in the ac76e in situ signal in the foxo null flies both in gastric ceca and in the CA (Fig. 3, compare panels C and D).…”
Section: Resultsmentioning
confidence: 99%
“…The foxo null foxo 25 strain and its littermate control, EP-147, are described in reference 20 and DI-11-Gal4 in reference 2. To produce UAS-AC76E transgenic flies, the coding region of ac76e tagged with a three-hemagglutinin (HA)-tag sequence in its C terminus was cloned into the p[UAS] vector.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation